Optimal Payment Contracts in Trade Relationships - Christian Fischer (ZBW - Leibniz Information Centre for Economics, 2020)
We study a seller's trade credit provision decision in a situation of repeated contracting with incomplete information over the buyer's payment propensity when the enforceability of formal contracts is uncertain. The payment terms of a transaction are selected in an inter-temporal trade-off between improving the quality of information acquisition and mitigating relationship breakdown risks. When contract enforcement institutions are weak, the optimal within-relationship provision dynamics of trade credit can be uniquely determined and depend on the share of patient buyers in the destination market as well as their access to liquidity. We obtain empirical evidence showing that in developing countries the relevance of trade credit in buyers' payment schedules has risen over-proportionally in recent years.
Keywords: L14; 330; Payment contracts; Trade credit; Trade dynamics; Relational contracts; Weak institutions